A case study on the rockfall assessment and stability analysis along Lengpui-Aizawl highway, Mizoram, India - Sardana S.; Sharma P.; Verma A.K.; Singh T.N. (My University, 2025)
Roadways are the lifeline for any city, especially in hilly regions. The increase in population and road constructions has led to the destabilization of the slopes resulting in mass movement. Anisotropic rockmass, whose behaviour is largely dependent on the planes of weakness, was simulated using 3DEC. The three-dimensional discontinuum modelling technique provides the most rigorous analysis of the failure process and deformation in the anisotropic rock. However, due to the limited capacity of the software, it is impossible to include all the discontinuities implicitly in numerical simulation. This paper provides a methodology for the application of Ubiquitous-Joint models on a field scale to include the anisotropic behaviour of rockmass. After identifying the failure-prone area using rigorous 3DEC slope stability analysis, rockfall analysis was also carried out to identify the maximum run-out, bounce height and total kinetic energy of falling rock blocks in the same section of the slope. 3DEC results show the maximum total displacement of 2.6 cm with a maximum velocity of 0.25 m/s, which confirms the instability in the slope. The rockfall simulation reveals that the falling rock blocks can hit the vehicle on the roadway with the kinetic energy of 58.5 kJ that makes this roadway unsafe. © 2021, Saudi Society for Geosciences.